Production management system (Hicom Teck See Manufacturing Maaysia Sdn. Bhd.) (Quality department) - Too, Wan Meng (2014)
The Production Management System (PMS) is special designed for manufacturing industry with the purpose to enhance efficient, effectiveness of stock traceability and data analysis at the production floor. It is also used to replace the manual system to trace stock and carry out analysis task which consume more time and work force. This system includes two modules which are of normal staff and admin. In order to develop a Production Management System for Hicom Teck See Manufacturing Malaysia Sdn. Bhd, Rapid Application Development (RAD) has been chosen. RAD has several characteristics that are suitable for the development of Production Management System. PHP and MySQL have been be used as programming language and database respectively for project development. In this project, using web-based will increase the efficiency and reduce human workload in Production Management System. This system was tested with unit testing, functionality testing, and user acceptance test. The results show the functionality of the system is passed which users satisfy with the system.